The Use Of Story Face Strategy In Improving The Student’s Reading Comprehension Of Recount Text At SMP Negeri 3 Mranggen - Dina Martsella Wulandari; Wiyaka Wiyaka; Fitri Yulianti (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
Story face is an adaptation of story mapping. The main purpose of this study was to find out whether there was a significant difference in the reading performance of the students between those who are taught by using the story face strategy and who are taught without using the story face strategy. This study used the quantitative research method with quasi-experimental design. The population was 8th grade junior high school and the sample was 60 students. To collect the data, researcher used test and applied  SPSS 27 to analyze the data. It was found that there is a difference in scores between the experimental and control groups. The experimental group's pre-test score was 62.73, and the post-test score was 81.00. There was an increase after receiving the story face strategy treatment. In addition, the control group's score was 62.67, and the post-test was 72.93. The experimental group scored higher. T-test using an Independent Sample Test with Asymp.Sig (2-tailed) value of 0.001 <0.050, so Ha is accepted, and Ho is rejected. T-table test results are df = 30+30-2=58. The researcher used the table of significant degree 5%, so the t-table was -1.671/+1.671. The t-test value surpassed the corresponding t-table value (5.380 > 1.671), and the p-value was 0.001, which is less than the significance level of 0.050. The results showed the effective application of the story face strategy in reading recount text. Students were able to improve their skills in reading comprehend with using story face strategy.